2019
DOI: 10.1002/brb3.1203
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors for cognitive impairment in the rural highly elderly

Abstract: Background Among the symptoms commonly faced by an increasingly aged population, dementia, preceded by cognitive impairment, most threatens their quality of life. Dementia is a well‐recognized burden, not only for individuals who face the disease and for their families, but also for entire nation. Aims The purpose of this study was to identify associated factors for cognitive impairment in a very elderly population via a screening study design in Sokcho, a rural area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
6
3
0
5
Order By: Relevance
“…Based on the results of this test, 113 (18.9%) participants were identified as the high-risk group, and the MMSE-DS score was lower in older adults without a spouse than the counterpart. This finding is consistent with that of a previous study [ 33 ] that older adults living alone exhibited lower MMSE-DS scores than those who did not live alone.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results of this test, 113 (18.9%) participants were identified as the high-risk group, and the MMSE-DS score was lower in older adults without a spouse than the counterpart. This finding is consistent with that of a previous study [ 33 ] that older adults living alone exhibited lower MMSE-DS scores than those who did not live alone.…”
Section: Discussionsupporting
confidence: 93%
“…likely to suffer from cognitive impairment. In line with our results, existing research also found that age and gender are both positively associated with lower cognition (stronger association was found among the female respondents) [8]. However, contrary to our results, living status was found to be a significant predictor of cognitive impairment [8].…”
Section: Socio-economic Inequalitiessupporting
confidence: 85%
“…The relationships between cognitive dysfunction, age, and education have been studied before. It has been shown that the prevalence of cognitive impairment decreased from 32.9% to 15.5% with a 3‐year increase in education time 38 . In our study, education levels of the COPD patients and the control group were similar.…”
Section: Discussionsupporting
confidence: 62%
“…It has been shown that the prevalence of cognitive impairment decreased from 32.9% to 15.5% with a 3‐year increase in education time. 38 In our study, education levels of the COPD patients and the control group were similar. This result eliminated the effect of education level on cognitive tests.…”
Section: Discussionsupporting
confidence: 58%